Antilithiatic effect of Peucedanum grande C. B. Clarke in chemically induced urolithiasis in rats. (24th December 2016) - Kumar, B.N.; Wadud, Abdul; Jahan, Nasreen; Sofi, Ghulamuddin; Bano, Humaira; Makbul, Shaikh Ajij Ahmed; Husain, Sadique
Abstract: Ethnopharmacological relevance: Duqu ( Peucedanum grande C. B. Clarke) has been used by Unani physicians since ancient times in retention of urine, renal and bladder calculi, nephritis and other associated disorders in different dosage forms. Aim of the study: The aim of the study was to evaluate the antiurolithiatic activity of Peucedanum grande C. B. Clarke in experimental model. Materials and methods: The experiment was carried out in male Sprague Dawley rats divided into 5 groups of 8 animals each. Animals of negative control received 1 ml of 5% Gum acacia throughout the study. Remaining four groups received Ethylene glycol 0.75% and Ammonium chloride 1% by adding in their drinking water for first seven days to induce urolithiasis. From 8th day, positive control received 1 ml of 5% Gum acacia, standard control received Cystone in the dose of 750 mg/kg while test groups A and B were treated with hydroalcoholic extract of test drug in the dose of 56 mg/kg and 97 mg/kg respectively up to 21 days, thereafter the animals were sacrificed. Number of CaOx crystals in urine, levels of serum calcium, phosphorus, creatinine, urea, urinary calcium and sodium were observed. Kidney homogenate analysis and histopathology were also carried out. Results: Test drug reduced number of CaOx crystals in urine (p<0.001); levels of serum calcium, phosphorus, creatinine, (p<0.001) urea, (p<0.05); urinary calcium (p<0.001) and sodium decreased significantly in standard and test groups. The urine volume increased significantly (p<0.05, 0.01) in both the test groups. Histopathology of kidney showed no CaOx crystal deposition in both the test groups. Conclusion: On the basis of above findings, it can be concluded that the test drug possesses significant antiurolithiatic activity. Graphical abstract: